Estimating fiscal reaction functions in Malaysia, Thailand and the Philippines - Lau, Evan; Lee, Alvina Syn-Yee (Penerbit Universiti Kebangsaan Malaysia, 2018)
As with most of the world economy, the 2008/09 global financial crisis has brought massive impacts on Southeast Asian economies. The debt/GDP ratios in most economies rose significantly, thus putting the spotlight again on fiscal sustainability. This article aims to distinguish the reaction of the primary balance/GDP to changes in the debt/GDP to assess the fiscal sustainability of Malaysia, Thailand, and the Philippines. In investigating how the respective governments react to the accumulation of debt, the article estimates the fiscal reaction function, initiated by Bohn (1998), using Ordinary Least Square (OLS) and Vector Autoregression (VAR). The empirical analysis reveals that, based on past behaviour, fiscal policy in Malaysia, Thailand, and the Philippines remains sustainable.